Football as a Form of Political Communication for St. Pauli Football Club Supporters - Kiki Esa Perdana (Universitas Jenderal Ahmad Yani, 2016)
The development of political communication has changed the conventional concept of politics and football. A broader understanding of political system and democracy has led football into something new, football is a new form of media and supporter is conveying a message. This article assesses how supporters use football as a medium for political purpose and how the involvement for supporters in the process. The results indicated that in the end, political communication is a process and affected by a political culture in society.